2023
DOI: 10.1002/cphc.202300231
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Chemical Properties of NiOx Thin Films: Oxygen Vacancy Formation in O2 Atmosphere

Raoul Blume,
Wolfram Calvet,
Aliakbar Ghafari
et al.

Abstract: NiOx films on Si(111) were put in contact with oxygen at elevated temperatures. During heating and cooling in oxygen atmosphere Near Ambient Pressure (NAP)‐XPS and –XAS and work function (WF) measurements, reveal the creation and replenishing of oxygen vacancies in dependence of temperature. Oxygen vacancies manifest themselves as a distinct O1s feature at 528.9 eV on the low binding energy side of the main NiO peak as well as by a distinct deviation of the Ni2p3/2 spectral features from the typical NiO spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…As reported in detail in our study of oxygen vacancy formation on NiO x thin films, such vacancies can readily form by thermal treatment in an oxygen atmosphere. 19 Increasing the sample temperature leads to the removal of oxygen atoms from the lattice, just as in the common reduction process in a vacuum. Yet, in the presence of O 2 , a balance between removal and replenishment of oxygen atoms depends on temperature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As reported in detail in our study of oxygen vacancy formation on NiO x thin films, such vacancies can readily form by thermal treatment in an oxygen atmosphere. 19 Increasing the sample temperature leads to the removal of oxygen atoms from the lattice, just as in the common reduction process in a vacuum. Yet, in the presence of O 2 , a balance between removal and replenishment of oxygen atoms depends on temperature.…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations of bond lengths, charge densities and BEs revealed that the NiO 1− x peak can be directly related to the formation of oxygen vacancies, which leads to a relaxation of the atoms around a vacancy influencing the charge density and, consequently, the XPS BE of these neighboring atoms. 19 Hence, the peak at 528.9 eV was labeled NiO 1− x . The other peak at 530 eV is ascribed to the presence of oxygen vacancies with chemisorbed OH, thus representing NiO 1− x –OH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations